Penerapan Waktu Siklus Singkat pada Granular Activated Carbon Sequencing Batch Reactor (GAC-SBR) untuk Pengolahan Limbah Cair Rumah Makan - Nur Anisah; Novirina Hendrasarie (Jurnal Serambi Engineering, 2022)
Has resulted in the generation of restaurant wastewater also increasing. Restaurant wastewater contains pollutants BOD, COD, TSS, Total-N, PO4, oil and grease with high enough levels so that it might pollute the environment if discharged into river bodies without going through a processing process. In this study, an experiment was conducted by applying granular activated carbon - sequencing batch reactor to treat restaurant wastewater. In this study was operated the reactor with short HRT of 6, 9, and 12 hours and compared with a comparison HRT of 36 hours. In the reaction phase, a GAC mass of 0.4 and 2.5 grams was added. The highest allowance for BOD is 91.23%, COD is 93.35%, TSS is 98.94%, PO4 is76.60 %, Total-N is 89.78%, and oils and grease are 99,99%. GAC was affixed during the reaction phase with a mass variation of 0.4 grams and 2.5 grams, the optimal GAC mass was obtained at a GAC mass of 0.4 grams. The aeration rate was operated at a rate of 20 and 40 L/min, the optimal aeration rate was obtained at a rate of 20 L/min.